STRATEGI GURU PENDIDIKAN AGAMA ISLAM UNTUK MENUMBUHKAN NILAI-NILAI PROFIL PELAJAR PANCASILA SISWA KELAS VII SMP NEGERI 2TANJUNG PURA - Humairoh (STAI Jama'iyah Mahmudiyah Tanjung Pura, 2024)
The application of the dimensions of Pancasila Student Character especially in the dimensions of faith, piety to God Almighty, and good morals has not been optimally carried out by teachers of Islamic religious education. This is evidenced by the non-optimal efforts made by PAI teachers to increase these dimensions. This dimension includes religious ethics,personal ethics, ethics towards humans ethics towards nature, and national ethics. The research approach used is a qualitative method with a case study type. Information collection was carried out through interviews, observation, and recording. Participants in this study consisted of school principals, PAI teachers and SMP Negeri 2 Tanjung Pura students. The research data were then analyzed using the Miles and Huberman analysis methods which included data reduction, data presentation, and drawing conclusions. Based on the data analysis carried out, it can be concluded that, (1) the teaching methods applied by PAI teachers in shaping the character of Pancasila students who believe, fear God Almighty, and have noble character are not only carried out in class, but also through examples of behavior and good character building. (2) Furthermore, the impact of the PAI teaching method on thec haracter of Pancasila students who believe, fear God Almighty, and have noble character is focused on preparation students to go directly into the world of work, industry, and business. Therefore, the role of good morals is very important in supporting student competence.